PENGARUH GAYA MENGAJAR INTERAKSIONAL GURU TERHADAP MINAT BELAJAR PESERTA DIDIK KELAS VIII PADA MATA PEAJARAN PENDIDIKAN AGAMA ISLAM DI SMPN 36 MAKASSAR: Penelitian Kuantitatif - Rasyid, Muhammad; Syahid, Akhmad; Nengsih, Ratika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study discusses the “Effect of Teacher Interaction Teaching Style on Learning Interest of Class VIII Students in Islamic Religious Education Subjects at SMPN 36 Makassar”. This research aims to find out: Interactional teaching style of Islamic Religious Education teachers in class, learning interest of class VIII students in Islamic Religious Education subjects, and the effect of interactional teaching style of Islamic Religious Education teachers on learning interest of class VIII students at SMPN 36 Makassar. The method used is quantitative research method. The population in this study were VIII grade students with a total of 123 students. The sample used was 56 respondents. The results of this study indicate that the implementation of the teacher's interactional teaching style applied is in accordance with the junior high school level. Based on the results of descriptive analysis with 56 respondents, it can be seen that the average student interest in learning is 88.85 with a standard deviation of 4.190 with a percentage of 57% in the moderate category. The effect of the teacher's interactional teaching style on the learning interest of class VIII students in Islamic Religious Education subjects at SMPN 36 Makassar partially is (1) the variable of the teacher's interactional teaching style obtained a significance value <0.05 (0.001 <0.05) and t_hitung = 5.473> t_table = 3.205, meaning that there is a significant effect partially. The simultaneous effect obtained a value of 0.222 with a percentage of 22.2%.